Answers

2015-04-24T23:01:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x^2-2x-15=0
Simply replace x by \frac{x}{2} to get an equation whose roots are 2 times the roots of above equation :
\left(\frac{x}{2}\right)^2-2\left(\frac{x}{2}\right)-15=0
\frac{x^2}{4}-x-15=0
x^2-4x-60=0
0
2015-04-25T03:52:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
  P(x)  =  x² - 2 x - 15  = 0    has solutions (roots) : α and β.
   Sum of roots = - coefficient of x: =>   α + β = 2
   product of roots = constant term  =>   α β = - 15

     then 2α + 2β = 4      and  2α * 2β  = -15 * 4 = - 60

quadratic polynomial :  x² - (sum of roots) x + product of roots.
  The quadratic polynomial :  x² - 4 x - 60

2 4 2